2018
DOI: 10.1038/s41598-018-24380-5
|View full text |Cite
|
Sign up to set email alerts
|

HadD, a novel fatty acid synthase type II protein, is essential for alpha- and epoxy-mycolic acid biosynthesis and mycobacterial fitness

Abstract: Mycolic acids (MAs) have a strategic location within the mycobacterial envelope, deeply influencing its architecture and permeability, and play a determinant role in the pathogenicity of mycobacteria. The fatty acid synthase type II (FAS-II) multienzyme system is involved in their biosynthesis. A combination of pull-downs and proteomics analyses led to the discovery of a mycobacterial protein, HadD, displaying highly specific interactions with the dehydratase HadAB of FAS-II. In vitro activity assays and homol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 55 publications
(69 reference statements)
9
41
0
Order By: Relevance
“…1C). The viability of the resulting mutant strain showed that hadD Mtb is not essential for the survival of Mtb in axenic culture, similar to the situation seen for hadD Msm in M. smegmatis 16 . This is consistent with the prediction of non-essentiality of hadD Mtb made from a microarray-based study 20 , but in discrepancy with a more recent survey using high-resolution phenotypic profiling where hadD Mtb was predicted to be essential 21 .…”
Section: Tuberculosis Holds a Putative Hadd Ortholog That Is Not Esupporting
confidence: 61%
See 4 more Smart Citations
“…1C). The viability of the resulting mutant strain showed that hadD Mtb is not essential for the survival of Mtb in axenic culture, similar to the situation seen for hadD Msm in M. smegmatis 16 . This is consistent with the prediction of non-essentiality of hadD Mtb made from a microarray-based study 20 , but in discrepancy with a more recent survey using high-resolution phenotypic profiling where hadD Mtb was predicted to be essential 21 .…”
Section: Tuberculosis Holds a Putative Hadd Ortholog That Is Not Esupporting
confidence: 61%
“…In a recent survey, a combination of pull-downs, using the dehydratase HadAB of FAS-II as a bait, and proteomic analyses led to the discovery of a novel (R)-specific dehydratase, HadD Msm , of the FAS-II system from M. smegmatis, a non-tuberculous mycobacterium 16 . HadD displays highly specific interactions with HadAB.…”
mentioning
confidence: 99%
See 3 more Smart Citations